Record-Making and Record-Keeping in Early Societies - Yeo, Geoffrey (2021)
Record-Making and Record-Keeping in Early Societies provides a concise and up-to-date survey of early record-making and record-keeping practices across the world. It investigates the ways in which human activities have been recorded in different settings using different methods and technologies.Based on an in-depth analysis of literature from a wide range of disciplines, including prehistory, archaeology, Assyriology, Egyptology, and Chinese and Mesoamerican studies, the book reflects the latest and most relevant historical scholarship. Drawing upon the author's experience as a practitioner and scholar of records and archives and his extensive knowledge of archival theory and practice, the book embeds its account of the beginnings of recording practices in a conceptual framework largely derived from archival science. Unique both in its breadth of coverage and in its distinctive perspective on early record-making and record-keeping, the book provides the only updated and synoptic overview of early recording practices available worldwide.Record-Making and Record-Keeping in Early Societies will be of interest to academics, researchers, and students engaged in the study of archival science, archival history, and the early history of human culture. The book will also appeal to practitioners of archives and records management interested in learning more about the origins of their profession.